Geographic variation in chemical composition in roseroot (Rhodiola rosea) in Finnmark County - Fjelldal, Erling; Svenske, Marianne; Martinussen, Inger; Volodin, Vladimir; Galambosi, Bertalan (Bioforsk, 2010)
v ok